Bentuk Kekerasan dalam Pengasuhan Anak Usia Dini pada Keluarga Ekonomi Menengah Kebawah di Desa X Kabupaten Bandung Barat - Reuhulina Putri Perangin Angin; Erhamwilda; Nurul Afrianti (Bandung Conference Series: Early Childhood Teacher Education, 2022)
Abstract. The purpose of this thesis is to determine the form of violence committed by parents in parenting. This thesis uses quantitative approach with survey method. The object of this thesis were lower-middle economic parent who had an early age children which consisted of 50 people. This thesis uses questionnaire and interview instrument. The result showed form of violence against early childhood in lower-middle economic familiy in X Village, West Bandung: the result is low. Average indicator is considered low. As for moderate violences, there is variable verbal violence indicator by insulting children with the result of 50 people (100%), ignoring children with the result of 27 people (54%), and scolding children with the result of 36 people (72%). This shows that although the result of the study showed that violence against children in the X Village, West Bandung was low, it does not mean parents do not commit violence against children, which can be seen in each indicator there are parents who still do violence, especially verbal and physical violence. Abstrak. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey. Populasi penelitian ini adalah orang tua berekonomi menengah kebawah yang mempunyai anak usia dini yang berjumlah 50 orang. Penelitian ini menggunakan instrumen kuesioner dan wawancara. Hasil dalam penelitian ini menunjukan bentuk kekerasan terhadap anak usia dini pada keluarga ekonomi menengah kebawah di Desa X Kabupaten Bandung Barat: hasilnya adalah rendah. Rata-rata indikator masuk kedalam kategori rendah. Adapun kekerasan yang hasinya sedang, ada pada variabel kekerasan verbal indikator menghina anak 50 (100%), mengabaikan anak 27 (54%), dan memarahi anak 36 (72%). Hal ini menunjukan bahwa walaupun hasil pada penelitian menunjukan kekerasan pada anak di desa X Kabupaten Bandung Barat itu rendah namun bukan berarti orang tua tidak melakukan kekerasan terhadap anak, terliah pada tiap indikator terdapat orang tua yang masih melakukan kekekrasan terutama kekerasan verbal dan fisik.